MEASURING THE EFFICIENCY OF WAQF FUND IN INDONESIA - Rusydiana, Aam Slamet; Sukmana, Raditya; Laila, Nisful (Journal of Islamic Monetary Economics and Finance, 2022)
This research measures the efficiency of waqf funds managed by philanthropic institutions in Indonesia using the Data Envelopment Analysis (DEA) approach over the 2013-2021 period. The unit of analysis consists of nine philanthropic waqf institutions. In the measurement of efficiency, the study takes human resource expenses and operational costs as inputs and collection and distribution of waqf funds as outputs. The findings indicate that the efficiency of philanthropic organizations in handling waqf funds varies from year to year between 2013 and 2021. The paper also notes that the Covid pandemic has no substantial impact on the efficiency of the waqf institutions. Interestingly, regional institution clusters are more efficient than mass organization and national institution clusters. Acknowledgment The authors would like to thank the Faculty of Economics and Business, Airlangga University, Indonesia, for the support that made this study possible